1991
DOI: 10.2307/1941851
|View full text |Cite
|
Sign up to set email alerts
|

Modifying Scent‐Marking Behavior to Reduce Woodchuck Damage to Fruit Trees

Abstract: Woodchucks (Marmota monax) damage fruit trees by gnawing on main stems during scent marking, a behavior unrelated to feeding. I tested whether damage could be reduced by providing alternative sites for scent marking or by applying predator odor to trees. Nearly all hardwood stakes supplied as alternative sites for scent marking were used, and the elapsed time from activation of a burrow until onset of damage to an adjacent tree was significantly greater for sites with stakes. However, the mean level of damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…First, P. polionotus may have been unable to discriminate among the scents used in the present study, either because P. polionotus is incapable of discriminating among scents of predators, deer, and water, or because the scents we used were not representative of the scents of predators and thus elicited no response. There is ample evidence from laboratory and controlled field settings that rodents can discriminate among predator scents (see Herman and Valone, 2000;Jedrzejewski et al, 1993;Kats and Dill, 1997;Parsons and Bondrup-Nielsen, 1996), including L. rufus (Swihart, 1991), V. vulpes (Dickman, 1992;Rosell, 2001;Sullivan et al, 1988), and C. latrans (Nolte et al, 1994). Moreover, in another study, we found that P. polionotus removed fewer seeds in experimental landscapes where L. rufus urine was applied over a 2-week period (Brinkerhoff RJ, unpublished data).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…First, P. polionotus may have been unable to discriminate among the scents used in the present study, either because P. polionotus is incapable of discriminating among scents of predators, deer, and water, or because the scents we used were not representative of the scents of predators and thus elicited no response. There is ample evidence from laboratory and controlled field settings that rodents can discriminate among predator scents (see Herman and Valone, 2000;Jedrzejewski et al, 1993;Kats and Dill, 1997;Parsons and Bondrup-Nielsen, 1996), including L. rufus (Swihart, 1991), V. vulpes (Dickman, 1992;Rosell, 2001;Sullivan et al, 1988), and C. latrans (Nolte et al, 1994). Moreover, in another study, we found that P. polionotus removed fewer seeds in experimental landscapes where L. rufus urine was applied over a 2-week period (Brinkerhoff RJ, unpublished data).…”
Section: Discussionmentioning
confidence: 81%
“…Olfactory predator cues are known to affect the behavior of a variety of organisms (Kats and Dill, 1997), including P. polionotus (Brinkerhoff RJ, unpublished data), Peromyscus spp. (Nolte et al, 1994), and other rodents (see Jedrzejewski et al, 1993;Kats and Dill, 1997;Sullivan et al, 1988;Swihart, 1991). In addition to four types of predator urine, urine of white-tailed deer, Odocoileus virginianus, was used as a urine control, and water was used as a nonurine control.…”
Section: Experimental Designmentioning
confidence: 99%
“…The effectiveness of predator odors as natural repellents may depend on such factors as the geographic distribution of predator and prey, the duration of their geographic association, and cultural transmission of predator responses among prey (Swihart 1991). An innate response by prey to a predator cue such as odor is likely to occur if prey and predator have coexisted over evolutionary time (e.g., Barreto and Macdonald 1999).…”
Section: Discussionmentioning
confidence: 99%
“…One implication may be that predator odors could reduce damage to human interests such as gnawing ears of growing corn and the bark of trees, providing a humane, environmentally acceptable substance that can be used to manage wild gray squirrel populations. In field trials, predator odors have succeeded in reducing feeding damage caused by a few species by 60-100% for periods ranging from 1 to 5 months (Sullivan and Crump 1984;Sullivan 1986;Sullivan et al 1988;Swihart 1991). However, no repellent is likely to provide total protection.…”
Section: Discussionmentioning
confidence: 99%
“…Prey may reduce these costs by assessing the risk of a predator being present from its odor. Avoidance of predator odor can be either species-specific (e.g., Swihart 1991) or general (e.g., Nolte et al 1994). Furthermore, some prey learn to respond only to predators that are actively dangerous (Dickman 1992).…”
Section: Introductionmentioning
confidence: 99%